2007
DOI: 10.1111/j.1439-037x.2007.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Stress on Some Physiological and Photosynthetic Parameters at Three Different Temperatures in Six Soya Bean (Glycine max L. Merr.) Cultivars

Abstract: IntroductionDuring their growth and development, plants are exposed to abiotic (high and low temperature, salinity, drought, radiation, etc.) and biotic (pathogen, fungus, etc.) stress factors, which decrease their yield and the quality of their products. To date, 20 %, 26 % and 15 % of suitable agricultural areas worldwide are affected by mineral, drought and temperature stresses respectively (Blum 1985, Ashraf 1994a, Flowers and Yeo 1995. In addition, there is a decay of 2 million ha of world agricultural la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 74 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…As with chlorophyll content, carotenoid amounts reduced in relation to salt treatments ( Figure 3B). Previous studies have shown that carotenoid content of leaves decreased due to salt stress (Çiçek and Çakırlar, 2008;Cha-um and Kirdmanee, 2009;Cambrollé et al, 2011). The reason for the decrease in pigment contents could be the increasing levels of ROS and the loss of membrane integrity.…”
Section: Cultivarsmentioning
confidence: 93%
See 2 more Smart Citations
“…As with chlorophyll content, carotenoid amounts reduced in relation to salt treatments ( Figure 3B). Previous studies have shown that carotenoid content of leaves decreased due to salt stress (Çiçek and Çakırlar, 2008;Cha-um and Kirdmanee, 2009;Cambrollé et al, 2011). The reason for the decrease in pigment contents could be the increasing levels of ROS and the loss of membrane integrity.…”
Section: Cultivarsmentioning
confidence: 93%
“…In many studies it was reported that salinity affected plant nutrients (Na , growth, membrane integrity, osmotic adjustment, photosynthetic activity, and antioxidant activity (M'rah et al, 2006;Çiçek and Çakırlar, 2008;Ejaz et al, 2012;Shahzad et al, 2012).…”
Section: +2mentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity, drought and heat stress events are major abiotic stress types that affect crop growth and development, and consequently biomass production, yield and quality (Çiçek & Çakirlar 2008; Zhu et al 2016). Salinity affects 20% of the global irrigated area (62 million ha) worldwide and reduces the productivity of food crops (Qadir et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Species‐ or variety‐specific factors, or the intensity and duration of the stress treatments can lead to different results. Çiçek & Çakırlar () found that the effects of salt stress and temperature on soybean photosynthetic parameters varied greatly between cultivars and stress intensity. In Jatropha curcas , the combination of salt (NaCl 100 m m ) with a heat stress treatment of 43 °C (which is stronger than the 35 °C used in Rivero et al .…”
mentioning
confidence: 99%